Determinants of macroeconomic variables on stock market return in Malaysia: FTSE KLCI / Nur Fatin Aqila Alam Shah - Alam Shah, Nur Fatin Aqila (Faculty of Business and Management, 2020)
The study has been examined the impacts of macroeconomic variables on stock market return in Malaysia: FTSE KLCI using the quarterly data from Q1 2008 to Q4 2018 which contains the total of 41 observations. More specifically, this study aims to investigate the current literature reviews by including the CPI, EXR, INT, COP and MON towards to the stock market return in Malaysia: FTSE KLCI. Furthermore, this study applied several empirical tests such as unit root test, normality test, descriptive statistics, multicollinearity test, autocorrelation test and multiple linear regression models. In conclusion, the result obtained from multiple linear regression shows that EXR, INT, COP and MON have significant and positive relationship while CPI has negative and insignificant relationship with the stock market return in Malaysia: FTSE KLCI.